Isolamento e seleção de bactérias lipolíticas provenientes de água residual de abatedouro - Ferreira, Camila Míryan de Oliveira (Universidade Federal Rural do Semi-Árido, 2015)
The growing interest in the production of lipases relates especially to the great biotechnological potential that these enzymes have. Lipases are enzymes that catalyze the hydrolysis of long chain triglyceride transforming them into glycerides and fatty acids. Microbial lipases have been addressed in constituting one of the most important groups of enzymes for biotechnological applications in several industrial sectors. Because of the promising potential of these enzymes and knowing that microorganisms use oils and fats as a carbon source for the production of lipases, this study aimed the isolation of lipase-producing bacteria from wastewater samples slaughterhouse through enrichment and growth in culture medium. A total of 68 morphologically distinct strains were recovered throughout the experiment. Subsequently, the lipase producing strains were selected by enzyme assay with the fluorescent dye Rhodamine B, which results in a fluorescent complex by the production of lipases in the plates. The results showed nine promising strains in the enzymatic test: ABAD01, ABAD05, ABAD07, ABAD09, ABAD12, ABAD17, ABAD20, ABAD21 and ABAD23. Likewise, reflecting the importance of studying the biotechnological potential of the microbial community associated to environments with high lipid content for the study of strains that produce lipases, with applications in the industry and in animal production
Isolation and selection of lipolytic bacteria from wastewater slaughterhouse
Keywords: Enzima; Lipase; Bactéria; Abatedouro; Enzyme; Lipase; Bacteria; Slaughterhouse; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL